Cardiac arrest in special circumstances. Issue 6 (20th December 2021) - Lott, Carsten; Truhlár, Anatolij
Abstract : Purpose of review: European Resuscitation Council Guidelines for Cardiopulmonary Resuscitation prioritize treatments like chest compression and defibrillation, known to be highly effective for cardiac arrest from cardiac origin. This review highlights the need to modify this approach in special circumstances. Recent findings: Potentially reversible causes of cardiac arrest are clustered into four Hs and four Ts (Hypoxia, Hypovolaemia, Hyperkalaemia/other electrolyte disorders, Hypothermia, Thrombosis, Tamponade, Tension pneumothorax, Toxic agents). Point-of-care ultrasound has its role in identification of the cause and targeting treatment. Time-critical interventions may even prevent cardiac arrest if applied early. The extracorporeal CPR (eCPR) or mechanical CPR should be considered for bridging the period needed to reverse the precipitating cause(s). There is low quality of evidence available to guide the treatment in the majority of situations. Some topics (pulmonary embolism, eCPR, drowning, pregnancy and opioid toxicity) were included in recent ILCOR reviews and evidence updates but majority of recommendations is based on individual systematic reviews, scoping reviews, evidence updates and expert consensus. Summary: Cardiac arrests from reversible causes happen with lower incidence. Return of spontaneous circulation and neurologically intact survival can hardly be achieved without a modified approach focusing on immediate treatment of the underlying cause(s) of cardiac arrest.